PRODUCT COUNT SYSTEM (International Journal of Food and Nutritional Sciences, 2023)
Industrial production lines churn out products from raw materials all the time But keeping these lines running smoothly is a very difficult task. There are many processes running together, which can lead to manual errors The production line has different processes, and the products produced need to be counted manually from one time to track and then sent to the next departmentThe human calculation of infinite products is impossible for humans. Someone inevitably lost track of him once. Here we have created an automated trading product to fulfil this taskThis system provides the following Advantages:• Automated Tireless counting• Keep Count Data Stored as well as Display live count• No Error probability in counting